政治革命下的教育變革：民國初期教育制度的再造（1912-1916） Educational Transformation During the Political Revolution: Restructuring the Education System in Early Republican China (1912-1916) - 周愚文 Yu-Wen Chou (National Taiwan Normal University, 2023)
以往教育研究多注意國家太平時期的發展，較少關注政局動盪下的教育變革。1912年1月中華民國建立，但因民初政局未穩，為因應開學所需，新設教育部只得儘速修改前清癸卯學制後發布命令施行；之後再新頒教育宗旨、學校系統、各級教育令及課程標準。最初教育部曾想另訂新制，但後迫於復學時間緊湊，只能修改舊制。再者，新訂學校系統仍是以前清學 制為基礎而稍修訂。本研究旨在探討民初辛亥革命後至袁氏稱帝前（1912-1916年）教育制度的再造，採史學方法，根據政府檔案、法規、公報、教育報刊及時人文集等一手資料，經內、外部考證後，探討教育制度調整的原因、經過、實施狀況及影響因素。研究發現，當時地方未能完全落實新制，其原因除政局不穩、戰事迭起外，原仿日學制持續發揮影響力、中央及地方經費支絀、地方教育行政體制殘破及中央地方爭權，均影響新制改革與落實。最後，研究指出政治革命後，舊有教育制度不必然也遭推翻，政府往往仍沿用後再修改，策略上是「穿衣改衣」，而無法另起爐灶。此段國家動盪時期的教育變革經驗，值得今後欲採革命式教育改革策略決策者關注。 The state of education during tumultuous times has often been overlooked by educational historians. However, such periods warrant attention because educational opportunities can be severely limited during these times. The fall of the Ch'ing dynasty in October 1911 led to the establishment of the Republic of China. Although a provisional Republican government was inaugurated in Nanking on January 1, 1912, the new democracy remained divided. A new Ministry of Education was established, and Dr. Yuan-Pei Tsai became its first minister. Tsai endeavored to replace the Ch'ing dynasty's existing K'uei Mao School System, instituted in 1904, with a new educational framework for the Republic. Because the government urgently wished to resume academic sessions by March of that year, a provisional general education regulation was promulgated through telegrams by the new ministry. The Republic was forced to adapt the Chi'ing dynasty's educational system, implementing emergency modifications such as renaming schools and principals, implementing a two-semester academic year, permitting coeducation in primary schools, removing the distinction between general and vocational secondary schools, revising primary and secondary school textbooks, and shortening the duration of secondary and normal school to 4 years. The effectiveness of the new regulations remained unclear because of ongoing conflicts between China's southern and northern governments. Reconciliation between the two factions led to superficial national unity in April. Subsequently, the Ministry of Education convened the Provisional Education Meeting in Peking, the new capital, in July 1912. President Shih-Kai Yuan announced new educational objectives and a reformed school system in early September, 2 months after the meeting. The revised educational goals emphasized moral, military and national, and aesthetic education. The new system comprised five educational stages: 4-year junior elementary school, 3-year senior elementary school, 4-year secondary school, 3-year prep-school, and 4-year university. This structure, although similar to the Ch'ing dynasty 4-5-4-3-3-4 model, had been streamlined to a 4-3-4-3-4 model; completing one's education from elementary school through university required a minimum of 18 years. A series of educational codes, regulations, and curricula were systematically introduced between 1912 and 1913, culminating in the establishment of the Jen Tzu K'uei Ch'ou School System. Regarding the historical narrative of educational reforms in early Republican China, the literature provides only a cursory overview of the new system; it does not delve into the complexities of the reform process or offer critical commentary. Employing a historical method, this study used first-hand sources, including documents from government archives, statutes, regulations, official gazettes, journals, and newspapers. This study employed both internal and external criticism to explore how the new central government sought to reconstruct China's educational system between 1912 and 1916; to analyze the causes, process, practices, and factors influencing these educational reforms; and to draw conclusions and implications. The major findings are as follows. The primary motivations for reforming the Ch'ing dynasty's educational system included its inefficiency, shortcomings, excessively long duration, improper curricula, and inconsistencies or redundancies across educational levels. Empirical evidence indicates that only 6 out of 18 provincial governments adopted the new statutes and regulations to implement the new educational system; the status of the remaining provinces remains unknown. Four major factors influenced these reforms. First, the Ch'ing school system, which was modeled after the Japanese system, continued to exert a considerable influence. Although the number of students who had graduated from Western countries increased after 1912, most had not focused on educational studies and consequently had limited understanding of Western educational systems. Second, ongoing political turmoil from 1913 to 1916, involving the rapid failure of the Second Revolution, the dissolution of China's parliament, the abolition of the constitution, the ascent and rapid descent of President Yuan as Emperor, the fleeting restoration of the Ch'ing dynasty, and the outbreak of civil wars among various warlords, severely hampered reform efforts. Third, the financial resources allocated to education by local governments were consistently inadequate, primarily due to the diversion of educational funds to military activities. In addition, the limited educational funds were often squandered by local educational agencies and schools. Finally, administrative disorganization and power struggles among provincial, local, and central governments negatively affected the implementation of the new system. The lessons from China's modern history indicate that completely abolishing an existing educational system is not strategically necessary for a new regime. In China, some revisions were made, and the old system continued to function. In understanding these reforms, consideration must be given to the fact that numerous provincial and central government officials visited Japan to gain educational insights after 1894. Additionally, a substantial number of Chinese students were studying in Japan at that time. These factors may have influenced the subsequent introduction of the Japanese education model into China. In the development of comparative education, modern China transitioned from what can be termed the "traveler's tale" stage to a stage of "educational borrowing." A comparison of the number of Chinese students studying in Japan and the US between 1906 and 1912 revealed that more students were in Japan. Moreover, these students displayed a deeper understanding of the educational system they were immersed in. During the Provisional Education Meeting of 1912, the participants who had received Japanese education outnumbered those of US and therefore likely had a greater influence on the final decisions. Notably, Hsi-Kuang Yau and Yi Chen, who were sent by Hu-Kuang Governor-General Chih-Tung Chang to inspect Japanese education in the late Ch'ing dynasty, played influential roles. Chen had even translated Japanese educational laws and drafted a framework for the K'uei Mao School System. Both individuals were official delegates, and therefore, their influence was substantial. Since 1922, the educational system established between 1912 and 1913 has been replaced by what is known as the New School System, which was modeled after the US 6-3-3-4 educational structure. In conclusion, the educational reforms of early Republican China offer valuable lessons for modern educational reformers. Adopting an evolutionary strategy rather than a revolutionary one, China reformed its education system during a period of political instability.